Action-guilt, survivor-guilt, and depression in combat-related PTSD - Mika Allyssa Esquillo; Riya Kumar; Elizabeth Ellen Morris; Christina Bass; Mary Turner; Gail Tillman; John Hart Jr; Michael A. Motes (PLoS ONE, 2026)
Identifying the role of guilt in post-traumatic stress disorder (PTSD) has important implications for understanding the development and treatment of PTSD. The present study is a secondary analysis of data collected on veterans with combat-related PTSD (N = 61) who enrolled in a clinical trial. Hierarchical regression analyses were used to explore associations between action- and survivor-guilt on the Clinician Administered PTSD Scale (CAPS), PTSD symptom severity on the CAPS, and depression on the Quick Inventory of Depressive Symptomatology (QIDS). Action- and survivor-guilt independently predicted PTSD total symptom severity, but in examining PTSD symptom cluster severity, only action-guilt independently predicted avoidance and numbing severity in PTSD. However, depression symptom severity on QIDS also mediated the association between action-guilt and PTSD total symptom severity and avoidance and numbing severity. Thus, action- and survivor-guilt appear to have independent contributions to PTSD symptom severity, and action-guilt, more specifically, appears to affect avoidance and numbing severity in PTSD through depression. The findings are discussed in terms of the potential role of guilt in PTSD and in relation to previous research on guilt and depression in PTSD and PTSD treatment.